The Influence of Physical Evidence, Relationship Marketing and Service Quality on Customer Purchase Interest in Cafe Mata Hati Kediri (Case Study on Students of University of Nusantara PGRI Kediri) - Rosfitasari, Fitri; Paramitha, Dyah Ayu (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim : This study aims to determine the effect of physical evidence, relationship marketing, quality service on customer buying interest in Kafe Mata Hati Kediri, with a focus on students of University of Nusantara PGRI Kediri. Mata Hati Cafe is located on Jl. Ahmad Dahlan No.34, Mojoroto, Kec. Mojoroto, Kediri City, East Java 64112. Design/Method/Approach : This research method is quantitative research with a descriptive approach using multiple linear regression tests. The population of this research is consumers of these MSMEs. This study involved 56 respondents as samples. Research Finding : The results showed that the influence of physical evidence, relationship marketing, and service quality simultaneously had a significant impact on customer buying interest. Practitionel/Policy implication : This research provides practical implications for cafe owners and management in improving customer experience and strengthening buying interest. Research limitation : The limitations of this study include a sample limited to students of University of Nusantara PGRI Kediri, so generalization of findings may be limited to that population.